Differential GABA(B)-Receptor-Mediated Effects in Perisomatic- and Dendrite-Targeting Parvalbumin Interneurons - Booker, Sam A. (Society for Neuroscience, 2013)
Inhibitory parvalbumin-containing interneurons (PVIs) control neuronal discharge and support the generation of theta- and gamma-frequency oscillations in cortical networks. Fast GABAergic input onto PVIs is crucial for their synchronization and oscillatory entrainment, but the role of metabotropic GABA(B) receptors (GABA(B)Rs) in mediating slow presynaptic and postsynaptic inhibition remains unknown. In this study, we have combined high-resolution immunoelectron microscopy, whole-cell patch-clamp recording, and computational modeling to investigate the subcellular distribution and effects of GABA(B)Rs and their postsynaptic effector Kir3 channels in rat hippocampal PVIs. Pre-embedding immunogold labeling revealed that the receptors and channels localize at high levels to the extrasynaptic membrane of parvalbumin-immunoreactive dendrites. Immunoreactivity for GABA(B)Rs was also present at lower levels on PVI axon terminals. Whole-cell recordings further showed that synaptically released GABA in response to extracellular stimulation evokes large GABA(B)R-mediated slow IPSCs in perisomatic-targeting (PT) PVIs, but only small or no currents in dendrite-targeting (DT) PVIs. In contrast, paired recordings demonstrated that GABA(B)R activation results in presynaptic inhibition at the output synapses of both PT and DT PVIs, but more strongly in the latter. Finally, computational analysis indicated that GABA(B) IPSCs can phasically modulate the discharge of PT interneurons at theta frequencies. In summary, our results show that GABA(B)Rs differentially mediate slow presynaptic and postsynaptic inhibition in PVIs and can contribute to the dynamic modulation of their activity during oscillations. Furthermore, these data provide evidence for a compartment-specific molecular divergence of hippocampal PVI subtypes, suggesting that activation of GABA(B)Rs may shift the balance between perisomatic and dendritic inhibition.